2024
DOI: 10.1037/spq0000573
|View full text |Cite
|
Sign up to set email alerts
|

The importance of treatment integrity: Examining the relationship between dosage and writing intervention outcomes.

Abstract: This study explored the relationship between 391 third-grade students' writing productivity and the amount of intervention dosage received over a 6-week period. In addition, the association between gender and the amount of intervention dosage received was examined. Results indicated that intervention dosage had a statistically significant relationship with students' writing productivity at the conclusion of intervention implementation. In addition, there was not a statistically significant difference in the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…G*Power 3.1.9.7 (Faul et al, 2007) was used to perform an a priori power analysis for a hierarchical regression analysis with two predictors. The effect size for this analysis was based on a pilot investigation examining the impact of dosage on students' writing productivity (Maguire & Eckert, 2023) and was entered into the power analysis with the following parameters: f = 0.15, α = .05, power = 0.80. The power analysis result indicated that 68 participants were needed per regression analysis.…”
Section: Research Design and Data Analysismentioning
confidence: 99%
“…G*Power 3.1.9.7 (Faul et al, 2007) was used to perform an a priori power analysis for a hierarchical regression analysis with two predictors. The effect size for this analysis was based on a pilot investigation examining the impact of dosage on students' writing productivity (Maguire & Eckert, 2023) and was entered into the power analysis with the following parameters: f = 0.15, α = .05, power = 0.80. The power analysis result indicated that 68 participants were needed per regression analysis.…”
Section: Research Design and Data Analysismentioning
confidence: 99%